Serological response to helminths in domestic animals - Soulsby, E. J. L. (The University of Edinburgh, 1952)
A study has "been made of the serological responses occurring in domestic animals as a result of natural infestation with helminth parasites. The helminth infestations studied were those of Fasclola hepatica. Cysticereus bovls. Ascaris lumhrlcoides, Dlctyocaulua vlviparus and Trichlnella spiralis. F.HEPATLCA: The serological response, as indicated by the precipitin test, in F.hepatlca infestation was most marked when the immature parasites were in their migratory phase. Thereafter the precipitin antibody level became lower. Specific complement fixation antibodies were demonstrated in the sera of only one infested animal. This was indicative that the complement fixation technique was unsuitable for the demonstrat¬ ion of antibodies in P,hepatica infestation. Alcoholic extracts of the parasite were found to give varying degrees of r.on specific complement fixation with sheep sera, irrespective of F.hepatica infestation. The miracidia of F.hepatlca were observed to suffer a lethal effect when placed in sheep serum. Complement was necessary for the reaction. Hypersensitivity, demonstrable by an JLOD# Intradermal test, was evident in a large percentage of animals infested with F.hepatica. In some cases this hypersensitivity was passively transferable, "by means of serum, to a non sensitive animal. Local skin desensitisation could "be produced to a marked degree hut generalised skin desensitisation was less obvious when large quantities of antigenic material were administered. G.BOVIS: Precipitin antibodies were demonstrated in the sera of animals which showed multiple eysticerci in the musculature. When only a few (1 or 2) eysticerci were present a serological response was frequently absent. Polysaccharide solutions of the parent parasite, T# saglnata# produced precipitin reactions with the sera of animals infested with P.hepatica only. This was thought to be due to an isoagglutinin like producing antigen present in both T.saginata and hepatlca. Animals infested with F#hepatica produced hypersensitive skin reactions to extracts of C.bovls# A common allergen In the two parasites was thought to be responsible# A.LUMBRIOOIDEA: Precipitin antibodies were demonstrated in the sera of pigs. These were found to bear no relationship to the presence of mature A.lumbricoides in the intestine# They did, however, show a relationship to the degree of chronic focal interstitial hepatitis. Hypersensitivity to extracts of A.lumbricoldes was evident in the majority of swine. This was similar to the precipitin reaction, in that it was related to the degree of chronic focal interstitial hepatitis but not to the presence of intestinal forms of A.lumbrlcolfles. D.VIVLNARUS: The majority of cattle examined showed skin hypersensitivity to D.vivlparue extracts. This hypersensitivity was most evident in the age group 2-j? to 3-j years. The hypersensitivity demonstrated occurred in the absence of parasites. Intestinal helminths did not influence the hypersensitive state. Hypersensitivity was demonstrated in sheep undergoing a sub-clinical infestation with 13.filaria Infestations with other lung worms produced a hypersensitive state which could be demonstrated by D.filaria extracts. This was indicative of a group reaction. T,SPIRALIS: Hypersensitivity to extracts of T.spiralis was demonstrated in only 5# 4$ of swine. Only 0.91 of swine showed marked reactions. Since these occurred in animals possessing marked hypersensitivity to A.lumbrlcoidea it was concluded that a strong hypt rsensitivity to A,lmribrlcoltl.es could sensitise pigs to extracts of T.spiralis. Infestations with T.trlchiura did not produce hypersensitivity to T.spiralis extracts. The use of animals at an abattoir afforded the opportunity to correlate the serological findings with post mortem evidence of infestation. Since the lack of helminth eggs in the faeces does not necessarily indicate absence of helminth infestation the post mortem examinations carried out gave a more complete picture of the parasitic burden. As a result it was found that light infestations or pathological evidence of helminth infestation could be correlated with the serological findings (vide P.hepatica. C.bovls and A.lumbrlcoldes). If faeces examination had been the sole criterion of evidence of infestation no correlation between serological findings and infestation would have been evident and false conclusions may have been drawn. The use of animals at an abattoir afforded the opportunity to correlate the serological findings with post mortem evidence of infestation. Since the lack of helminth eggs in the faeces does not necessarily indicate absence of helminth infestation the post mortem examinations carried out gave a more complete picture of the parasitic burden. As a result it was found that light infestations or pathological evidence of helminth infestation could be correlated with the serological findings (vide P.hepatica. C.bovls and A.lumbrlcoldes). If faeces examination had been the sole criterion of evidence of infestation no correlation between serological findings and infestation would have been evident and false conclusions may have been drawn.
A study of the serological response to helminths in domestic animals